2016
DOI: 10.1038/ncomms11315
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of metal-organic frameworks for molecular sieving membranes

Abstract: The development of simple, versatile strategies for the synthesis of metal-organic framework (MOF)-derived membranes are of increasing scientific interest, but challenges exist in understanding suitable fabrication mechanisms. Here we report a route for the complete transformation of a series of MOF membranes and particles, based on multivalent cation substitution. Through our approach, the effective pore size can be reduced through the immobilization of metal salt residues in the cavities, and appropriate MOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(98 citation statements)
references
References 50 publications
1
95
1
Order By: Relevance
“…In this case, the gas transport of MMM containing inorganic porous filler particles is determined via the Knudsen diffusion . The molecular diffusion mechanism is demonstrated for the MMM containing nanomaterial filler particles such as CMSs, zeolitic imidazolate frameworks, and MOFs . Finally, the gas transport through glassy polymers is completed by the solution‐diffusion mechanism .…”
Section: Methodsmentioning
confidence: 99%
“…In this case, the gas transport of MMM containing inorganic porous filler particles is determined via the Knudsen diffusion . The molecular diffusion mechanism is demonstrated for the MMM containing nanomaterial filler particles such as CMSs, zeolitic imidazolate frameworks, and MOFs . Finally, the gas transport through glassy polymers is completed by the solution‐diffusion mechanism .…”
Section: Methodsmentioning
confidence: 99%
“…A series of MOF–MOF composite membranes have been fabricated and shown impressive separation performances . Jeong et al proposed a heteroepitaxial growth method to fabricate continuous and well‐intergrown ZIF‐8–ZIF‐67 composite membranes ( Figure ), which were realized by first heteroepitaxial growth of ZIF‐67 membranes from nanosized ZIF‐8 seed layers, followed by heteroepitaxial tertiary growth of ZIF‐8 overlayers on prepared ZIF‐67 membranes .…”
Section: Microstructural Engineering Of Mof Membranes At a Mesoscopicmentioning
confidence: 99%
“…Prepared composite membranes exhibited unprecedentedly high separation factors of propylene over propane (≈200), possibly due to an enhanced grain‐boundary microstructure. Zhang et al reported a novel route for partial transformation of HKUST‐1 membranes into HKUST‐1–MIL‐100 composite membranes based on multivalent‐cation substitution under ambient conditions . Through this approach, pore apertures could be reduced through the immobilization of amorphous FeCl 3 residues in MIL‐100 cavities, and desired HKUST‐1 crystal facets could be exposed to provide competitive molecular sieving ability.…”
Section: Microstructural Engineering Of Mof Membranes At a Mesoscopicmentioning
confidence: 99%
“…And it is worthy to note the entrance size and pore size of MOF are not always the same. The entrance size is usually smaller than pore size, such as HKUST-1 [118,119] and ZIF-8 [120]. Several ZIF membranes have been reported for gas separation due to their high chemical stability [95,96,[120][121][122].…”
Section: Size Sieving Based Gas Transportationmentioning
confidence: 99%